The Influence of Social Media Marketing and Perceived Quality on Brand Loyalty Mediated by Trust (An Empirical Study on Chatime Customers in Jabodetabek) - Felicia Madelline (CV. Publikasi Indonesia, 2023)
The purpose of this research is to analyze the influence of social media marketing and quality perception on brand loyalty mediated by trust (empirical study on Chatime brand consumers in Jabodetabek). This research uses a quantitative approach and uses a structural equation model. The survey was conducted to respondents with the criteria of respondents being customers of Chatime. In this study, it was analyzed with Structural Equation Model (SEM) using AMOS program. The research results prove that social media marketing has a positive and significant effect on trust. Other results prove that quality perception has a positive and significant effect on trust, trust has a significant effect on brand loyalty, social media marketing has a positive and significant effect on brand loyalty and quality perception has a positive and significant effect on brand loyalty, social media marketing does not have a positive and significant effect on brand loyalty mediated by trust, and quality perception does not have a positive and significant effect on brand loyalty mediated by trust.